A flexible data schema and system architecture for the virtualization of manufacturing machines (VMM). (October 2017) - Angrish, Atin; Starly, Binil; Lee, Yuan-Shin; Cohen, Paul H.
Highlights: An Unstructured Data model to represent virtual twins of physical machines. Stacked architecture for the representation of a virtual manufacturing machine (VMM). Third-party apps through interaction with the VMM middleware. An operating system architecture for the control of various VMMs on a shop-floor. Abstract: Future factories will feature strong integration of physical machines and cyber-enabled software, working seamlessly to improve manufacturing production efficiency. In these digitally enabled and network connected factories, each physical machine on the shop floor can have its 'virtual twin' available in cyberspace. This 'virtual twin' is populated with data streaming in from the physical machines to represent a near real-time as-is state of the machine in cyberspace. This results in the virtualization of a machine resource to external factory manufacturing systems. This paper describes how streaming data can be stored in a scalable and flexible document schema based database such as MongoDB, a data store that makes up the virtual twin system. We present an architecture, which allows third-party integration of software apps to interface with the virtual manufacturing machines. We evaluate our database schema against query statements and provide examples of how third-party apps can interface with manufacturing machines using the VMM middleware. Finally, we discuss an operating system architecture for VMMs across the manufacturing cyberspace, which necessitates command and control of various virtualized manufacturing machines, opening new possibilities in cyber-physical systems in manufacturing.